Pengaruh Promosi Jabatan Terhadap Prestasi Kerja Karyawan Pada Rumah Makan Telaga Biru Kecamatan Merapi Barat - Wartono (Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study was to determine and prove the effect of a promotion to employees performance in Telaga Biru Restaurant. The benefis of this research to add insight and knowledge about how the amplication compiler accepted theory lectures bench with existing practices in employee Telaga Biru Restaurant Merapi. To discus the formulation of the problem mentioned above, in this study another the sampling method used in this study are saturated sampling is because population is small so all existing populations as samples used a qualitative analysis, quantitative analysis, Regression Analysis, Correlation Coefficient analysis, coefficient of determination and hypothesis testing. From simple linear regression calculation results obtained the equation Y = 4.589 + 0.65 x + e. This shows that the influence of promotion to employee performance is 0,65. And calculating the value of r = 0.60. This value indicates that there is a positive correlation between promotion and job performance and can be seen from the value of r. Coeficient of determination of KD = 0.34 or 34 of performance are influence by promotion and the remaining 66% is influenced by other factors. From the calculation of the value of t-test = 4.741 and t-table 2.023. So the value of t-test bigger than t-table (t count> t-table), this shows that the Hi Ho is rejected and accepted, which means there is a significant relationship between promotion to employees performance in Telaga Biru Restaurant. This means that promotion has a positive effect on Job in Telaga Biru Restaurant.